New species and a new record of sea cucumbers from deep waters of the South African temperate region (Echinodermata: Holothuroidea) - Thandar, Ahmed S. (Zootaxa, 2009)
Two new species, Pseudostichopus langeae and Psolus griffithsi, and a new South African record, Molpadia musculus Risso, are described from some deep-sea material collected off the South African west and south coasts. This material also contains the well known Pseudocnella insolens (Théel), Ocnus capensis (Théel), Rhopalodinopsis capensis Heding and an indeterminate Thyone sp.